Alterations of mitochondrial dynamics in serotonin transporter knockout rats: A possible role in the fear extinction recall mechanisms - Brivio, Paola; Gallo, Maria Teresa; Karel, Peter; Cogi, Giulia; Fumagalli, Fabio; Homberg, Judith R.; Calabrese, Francesca (Frontiers in Behavioral Neuroscience, 2022)
Stress-related mental disorders encompass a plethora of pathologies that share the exposure to a negative environment as trigger for their development. The vulnerability to the effects of a negative environment is not equal to all but differs between individuals based on genetic background makeup. Here to study the molecular mechanisms potentially underlying increased threat anticipation, we employed an animal model showing this symptom (5-HTT knockout rats) which we exposed to Pavlovian fear conditioning (FC). We investigated the role of mitochondria, taking advantage of the recent evidence showing that the dynamic of these organelles is dysregulated after stress exposure. Behavioral experiments revealed that, during the second day of extinction of the FC paradigm, 5-HTT knockout (5-HTT-/-) animals showed a lack of fear extinction recall. From a mechanistic standpoint, we carried out our molecular analyses on the amygdala and prefrontal cortex, given their role in the management of the fear response and due to their tight connection. We demonstrated that mitochondrial dynamics are impaired in the amygdala and prefrontal cortex of 5-HTT-/- rats. The dissection of the potential contributing factors revealed a critical role for the mechanisms regulating fission and fusion that are dysregulated in the transgenic animals. Furthermore, mitochondrial oxidative phosphorylation, as well as mitochondrial biogenesis and the production of antioxidant enzymes, were altered in these brain regions in 5-HTT-/- rats. In summary, our data suggest that increased extracellular 5-HT levels cause an unbalance of mitochondrial functionality that could contribute to the reduced extinction recall of 5-HTT-/- rats, pointing out the role of mitochondrial dynamics in the etiology of psychiatric disorders. Our findings, also, provide some interesting insights into the targeted development of drugs to treat such disorders.